Engaging synergetic pedagogical approaches for higher education: an innovative teaching plan for educators - Abd Hamid, Siti Nur Fathanah; Zaini, Muhammad Haziq; Wan Maizon, Wan Saidatul Nasuha; Ayob, Nor Azira; Abdullah, Farzana Izzati (Faculty of Administrative Science and Policy Studies, 2024)
The module titled 'Engaging Synergistic Pedagogical Approaches for Higher Education: A Teaching Plan for Educators' presents a pioneering framework for educators aimed at revolutionising higher education through interactive and student-centred teaching methods. In response to the fast-paced technological advancements and evolving educational requirements of our time, this initiative strives to bridge traditional teaching methods with contemporary demands. Its goal is to cultivate innovation within higher education, enabling students to develop crucial skills like critical thinking, problem-solving, and adaptability necessary for success in the 21st century. Drawing insights from small-scale research involving students, this initiative explores and implements pedagogical strategies that actively involve students in their learning process. The findings underscore the necessity for interactive teaching and learning experiences, which this innovative approach aims to address by leveraging technology, experiential learning, and collaborative projects to create a dynamic and immersive educational setting. Ultimately, 'Engaging Synergistic Pedagogical Approaches for Higher Education: A Teaching Plan for Educators' envisions a higher education landscape where innovation serves as a fundamental aspect of the learning journey rather than just a buzzword. By fostering creativity, critical thinking, and adaptability, this initiative aims to empower the future generation of leaders and problem solvers.